Historical-legal aspects of the influence of the Canons in the treatment of servitudes in Kosovo: The influence of the Canons in the treatment of servitudes in Kosovo - Aqifi, Berat (Acta Universitatis Danubius. Juridica, 2021)
Abstract: In this paper we will analyze the institute of law services in a broader historical-legal point of view, seeing it closely related to the principles of law in general, and Albanian customary law based on the Canons that acted in the face of a very large influence of the Roman law of that time, of the Byzantine Empire ("Nomos Georgikos"), of the laws of Ottoman law ("Sharia law"), which exercised their activity, and which had for conse-quently their influence in the areas where Albanians lived. Given the importance of the servitude as an integral part of the right to property, the circumstances in which it was created, the way it evolved since ancient times influenced by Roman law and the Albanian Canons, where you learn to important also in our law in particular, although it was not created by the right of ownership, it became an important derivative of it. From this paper we will try to give some answers due to some ambiguities that have influenced to date in the historical-legal aspect in the right of ownership in our country, regarding the shortcomings of the legal framework of real rights on foreign items to provide solutions to numerous cases and problems that arise in practice from their implementation influenced by the Albanian customary law transferred through the Canons. Of particular importance are the legal norms in the civil field, especially in the field of property rights and inheritance created in certain historical and geographical circumstances and conditions, where this right acted, also influenced the preservation of some features and elements of national nature. , in the face of the risk of assimilation and the numerous influence of foreign law. Of course, special attention is paid to the "Canons", as part of a special extension and value of Albanian customary law. Keywords: Canons, law, Roman law, servitude, usufructus.